Integrating Air Quality and Public Health Benefits in U.S. Decarbonization Strategies - Gallagher, Ciaran L.; Holloway, Tracey (Frontiers in Public Health, 2020)
Studies quantifying the air quality and associated human health “co-benefits” from climate mitigation strategies represent a growing area of research and policy analysis. Still, these studies are relatively sparse, reflecting the historical disconnect between literature quantifying the air quality and health, as compared to other aspects of climate and energy policy evaluation. While linkages between energy and transportation sector decarbonization and air pollution are qualitatively well established, quantifying the air quality co-benefits of climate, clean energy, and transportation electrification policies requires models and analysis methods that span social, physical, chemical, and biological systems. Studies in the peer-reviewed literature (n=32) have evaluated carbon pricing, renewable portfolio standards, energy efficiency, renewable energy deployment, and clean transportation. A number of major findings have emerged from these studies: 1) decarbonization strategies can reduce air pollution disproportionally on the most polluted days; 2) renewable energy deployment and climate policies offer the highest health and economic benefits in regions with greater reliance on coal generation; 3) monetized air quality health co-benefits can offset costs of climate policy implementation; 4) monetized co-benefits typically exceed the levelized cost of electricity (LCOE) of renewable energies; 5) climate mitigation strategies can have adverse effects on air quality; 6) Electric vehicle (EV) adoption generally improves air quality on peak pollution days, but can result in ozone disbenefits in urban centers due to the titration of ozone with nitrogen oxides. Drawing from these published studies, we review the state of knowledge on climate co-benefits to air quality and health, identifying opportunities for policy action and further research.